Ergonomic Park Erving Tools in Banyuurip Village Kedamean District - Mega Yuni A; Nurul Mazidah Z A; Muhammad Robby K; Awang Setiawan W (Kontribusia : Research Dissemination for Community Development, 2018)
One of the factors that influence on plant development is watering. Watering is an indispensable thing in keeping and caring for the plants to thrive. In Banyuurip Village, the entrepreneurs are still doing manual methods by using a water hose that is considered to be time consuming and less efficient. Adequate water demand is one of the most important things. If this is not addressed then it will be fatal for the development of the crop itself. The results of the work program organized by the Group 6 Industrial Engineering course by implementing an ergonomic garden sprinkler application can assist entrepreneurs in shortening time and more efficiently. It is recommended that ornamental garden or gardening equipment can be applied by all entrepreneurs of ornamental plants, and also the village government should be able to conduct an in-depth review so as to provide progress and mutual benefit for both community and government